LATIN AMERICAN ANTI-MARXISM: THE CASE OF HERNÁN FAIR - Alfaro Vargas, Roy (2013)
This article is the product of a reaction against Latin American anti-marxism, especially against Hernán Fair’s position, which attacks marxism from a perspective that reproduces some stereotypes of the period of Cold War. Also, I criticize the argumentation of Hernán Fair for considering it highly contradictory and linked to the interests of neoliberalism. In this process of criticizing Fair’s position, I argue against the postmodern and poststructuralist trends that hide the vision of truly compromise from the Latin American intellectuals and imply to assume authors as Lacan, Derrida, etc., in an unthoughtful way.